CLIMATE CHANGE AND ITS IMPACT ON MARINE BIODIVERSITY: A STUDY OF OCEAN ACIDIFICATION AND CORAL REEF HEALTH - Amina Zayed (Modern American Journals, 2025)
The ongoing changes in climate have led to a significant increase in atmospheric CO₂ levels, resulting in ocean acidification, a process that is having profound effects on marine biodiversity, particularly on coral reef ecosystems. Coral reefs, one of the most diverse ecosystems on the planet, are increasingly vulnerable to rising ocean temperatures and the decrease in ocean pH caused by increased carbon dioxide absorption. This paper explores the interconnectedness between ocean acidification, climate change, and the health of coral reef ecosystems, focusing on the impact of reduced pH levels on marine species' survival, reproduction, and overall biodiversity. We also examine the potential long-term consequences for human communities that depend on these ecosystems for food, tourism, and coastal protection. Through a synthesis of recent studies, this paper aims to provide a comprehensive understanding of the mechanisms by which climate change is reshaping marine life and the urgent need for mitigation and adaptation strategies to safeguard marine biodiversity.
Keywords: Climate Change, Marine Biodiversity, Ocean Acidification, Coral Reef Health, Carbon Dioxide, Marine Ecosystems, Ocean Temperature, Biodiversity Loss, Coastal Protection, Marine Conservation